Risk Assessment Method of UHV AC/DC Power System under Serious Disasters - Rishang Long; Jianhua Zhang (Energies, 2016)
Based on the theory of risk assessment, the risk assessment method for an ultra-high voltage (UHV) AC/DC hybrid power system under severe disaster is studied. Firstly, considering the whole process of cascading failure, a fast failure probability calculation method is proposed, and the whole process risk assessment model is established considering the loss of both fault stage and recovery stage based on Monte Carlo method and BPA software. Secondly, the comprehensive evaluation index system is proposed from the aspects of power system structure, fault state and economic loss, and the quantitative assessment of system risk is carried out by an entropy weight model. Finally, the risk assessment of two UHV planning schemes are carried out and compared, which proves the effectiveness of the research work.